KEBEBASAN BERAGAMA DALAM PERSPEKTIF ABDURRAHMAN WAHID - Damrizal Damrizal (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: Violence in the name of religion over the past decades continues to rise. Not only conflict involving inter-religious, but also occurs in internal religious communities that exist in Indonesia. The recognition of absolute truth (truth claims) in the propagation of religion, or a unilateral claim to the most correct opinion, assuming the other is wrong, in interpreting the sacred text of a religion is the seeds that at any moment can trigger the outbreak of the conflict. Awareness of nationality, including the reality of plurality, which framed the Unitary Republic of Indonesia based on Pancasila continue to be degraded in the midst of society that can no longer be a unifying pillar. The conditions there should be a serious concern by all parties in order to reduce collisions that occur in the community because of their difference in value or the existing norms. Few people pay attention to this issue is one of them, Abdurrahman Wahid. As a former NU chairman and former president, Abdurrahman Wahid, known as the protector of minorities, as part of its implementation in maintaining freedom. It is interesting to know what you think Abdurrahman Wahid on religious freedom. In this study, researchers used a qualitative approach. The method in analyzing the data with descriptive analysis, a method that addresses the issue by presenting findings from the research subjects to get a conclusion on the basis of theoretical studies that have been done before. Techniques of collecting data is with the research literature, namely the search for materials in the form of books, articles freelance or search the data by using the internet. The results of this study show religious freedom offered Abdurrahman Wahid is a consciousness that recognizes the diversity of Muslims and human diversity. Where each religion run sound belief. Islam as a religion of grace lil Alamin applied in real life, in which every citizen has the right to show their identity without any discrimination of any party. Understanding the implications of Religious Freedom was initiated by Abdurrahman Wahid Dapa felt by religious communities in Indonesia today. When religious people can coexist harmoniously and peacefully. Even against marginalized religious groups such as Shiite, Ahamadiyah and Confucian. Even Confucian become a religion of its own in the era of its leadership and make the Lunar day as a national holiday, as the implications of religious freedom that he woke up.